ANALISIS BIAYA PEMANENAN KAYU BULAT SISTEM KEMITRAAN HPH - KOPERASI DESA DI KALIMANTAN TENGAH - Zakaria Basari (Jurnal Penelitian Hasil Hutan, 2004)
To minimize illegal logging in natural production forest, one of concession forest in Kalimantan has initiated to do a joint bussines logging with a community wellfare cooperative. The aim of the study was to measure productivity of extraction, operation cost, joint bussines income, investament and income of Koperasi Desa.The observation area was located at PT Tanjung Raya Intiga (PT TRI), Barito Hulu Puruk Cahu Forest District, of Central Kalimantan Province in 2001.The results showed that logging production achieved was 892,9 m3, log extraction productivity 99 m3. hm/hour, operation cost Rp 14,227/m3, logs selling revenue Rp 31,235,950,-, investment cost Rp 2,901,017.- and cooperative income Rp 28,901,017.-.The financial income was distributed to local community (34%), wages for cooperative bussines managers (29%), village contribution (4,5%), administration fee for cooperative (5%) and government officers (27%).The local people and the forest concessioners could share the benefit of cooperation in naturalproduction forest management.